2013
DOI: 10.2190/pm.45.1.e
|View full text |Cite
|
Sign up to set email alerts
|

Does a Copycat Effect Exist in the Emergency Department?

Abstract: A copycat effect was found in ED-visiting suicide attempts. Prevention of re-attempts should be initiated in the ED. A specific action guide should be established for suicide attempts in the ED, including cooperation between other hospitals, the community, and the media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
(65 reference statements)
0
7
1
Order By: Relevance
“…Our results demonstrated no significant clinical differences (symptoms acuity, suicidal status, hospitalization rates) in presentation during the two weeks following both suicides compared to the two weeks before, except for acuity of mood symptoms, which barely reached significance. Interestingly, a recent Korean study that looked specifically at suicide attempts uncovered no significant difference between the number of suicide attempts before and after a celebrity suicide (Kim et al 2013). The finding that clinical severity of ED presentation was not affected in this study is important because it means that a greater number of youths with MH problems sought services; youths who may not have sought services otherwise.…”
Section: Discussioncontrasting
confidence: 50%
“…Our results demonstrated no significant clinical differences (symptoms acuity, suicidal status, hospitalization rates) in presentation during the two weeks following both suicides compared to the two weeks before, except for acuity of mood symptoms, which barely reached significance. Interestingly, a recent Korean study that looked specifically at suicide attempts uncovered no significant difference between the number of suicide attempts before and after a celebrity suicide (Kim et al 2013). The finding that clinical severity of ED presentation was not affected in this study is important because it means that a greater number of youths with MH problems sought services; youths who may not have sought services otherwise.…”
Section: Discussioncontrasting
confidence: 50%
“…Several studies have previously shown a rapid and sustained increase in suicide following a celebrity's completed suicide in Korea. 28 29 The strong effect of the media has been suggested as a reason for copycat suicides, and new media including Instagram are particularly important as potential risk factors for NSSI. 30 31 32 Although we could not delineate a causal relationship between increased SA or NSSI and social phenomenon or media in this study, improvement in media reporting and the implementation of preventive strategies for high-risk populations might be important in reducing harmful behaviors among adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated a copycat effect by analyzing suicide data after one or two celebrity suicides, examining suicide attempts in emergency departments and demonstrating the correlation of media coverage with overall changes of suicide number. 8 9 10 …”
Section: Introductionmentioning
confidence: 99%